2018
DOI: 10.1038/s41467-018-05101-y
|View full text |Cite|
|
Sign up to set email alerts
|

Electrically driven three-dimensional solitary waves as director bullets in nematic liquid crystals

Abstract: Electric field-induced collective reorientation of nematic molecules is of importance for fundamental science and practical applications. This reorientation is either homogeneous over the area of electrodes, as in displays, or periodically modulated, as in electroconvection. The question is whether spatially localized three-dimensional solitary waves of molecular reorientation could be created. Here we demonstrate that the electric field can produce particle-like propagating solitary waves representing self-tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(123 citation statements)
references
References 43 publications
11
111
1
Order By: Relevance
“…The overall director configuration and dynamics in the high-frequency dresses are thus similar to that of the director in 90 B h directrons reported in Ref. [4]. Because of that, we call a tangential sphere with a directron dress induced…”
Section: B Director Structure Of Directrons In High-frequency Fieldsupporting
confidence: 74%
See 3 more Smart Citations
“…The overall director configuration and dynamics in the high-frequency dresses are thus similar to that of the director in 90 B h directrons reported in Ref. [4]. Because of that, we call a tangential sphere with a directron dress induced…”
Section: B Director Structure Of Directrons In High-frequency Fieldsupporting
confidence: 74%
“…Electrically induced directron dresses around the spheres, however, bring about a necessary polar symmetry in the structure and render the tangentially anchored spheres electrophoretically active under the AC field. The structure of the directrons that form above some electric field threshold is similar to the directrons described for uniformly aligned nematics without colloids [4,5]. The directron-dressed spheres move in the plane perpendicular to E ; depending on the frequency or amplitude of the field, the spheres can move parallel, perpendicularly or at some angle to the uniform background director 0 n .…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…First, as previously reported for cuboidal inclusions dispersed in LC, we found that microcubes without and with DMOAP treatment diagonally aligned their bodies to n 0 and exhibited birefringent edges (Figure a,e), indicating that the near‐surface n deviates from n 0 (and thus from the optical axes of the polarizers). Second, when viewed with a retardation plate of wavelength λ = 530 nm with its slow axis ( s ) at 45° to the polarizers, a higher order interference color (blue; Figure b) was observed at the surfaces of native microcubes parallel to s , suggesting a planar alignment of n at the surface of the microbots (see inset in Figure b) . Conversely, the surfaces of DMOAP‐treated microcubes exhibited a lower order interference color (yellow; Figure f), suggesting a homeotropic alignment of n at the microbot surface.…”
Section: Resultsmentioning
confidence: 99%